The Moderating Role of Principal's Effective Leadership on Service Quality Towards Vocational High School Teachers' Satisfaction - Kholil , Ahmad; Rokhman , Fathur; ., Masrukhi; Utomo , Cahyo Budi; Widiyono , Didik (Journal of Ecohumanism, 2025)
Vocational education is expected to be at the forefront in producing graduates who are useful and effective for society and the nation. Human resources, particularly teachers, must be prioritized as a key factor in determining the success of the learning objectives in schools. The objectives of this research are: (1) to determine the direct effect of service quality and effective school leadership on teacher job satisfaction; (2) to examine the moderating effect of school leadership in enhancing service quality to improve teacher job satisfaction in vocational schools. This study uses a quantitative research approach with an ex post facto model. The research population and sample consist of 187 teachers from vocational high schools (SMK). The findings of the study indicate that: (1) service quality has a significant positive effect on teacher job satisfaction in SMKs; (2) effective school leadership has a significant positive effect on teacher job satisfaction in SMKs; (3) the moderating variable of effective school leadership strengthens the impact of service quality on teacher job satisfaction. This study recommends that vocational schools improve service quality and develop effective school leadership to achieve the school's vision, mission, goals, and objectives.